Exploring students’ word learning strategies in project based learning activities - Anggraini Anggraini; Miftah Al Farhan (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2023)
Vocabulary plays a crucial role in English language learning. Hence, students should have certain strategies to obtain sufficient vocabularies to facilitate their language learning. Word-learning strategies are ones that students can use to help them learn vocabularies more optimally. Therefore, this study aims to identify students’ word-learning strategies and the obstacles they encounter during project-based learning activities. A case study method was employed to obtain the data using an in-depth interview and direct observation in the classroom. Six students and one English teacher were involved as research participants. The results identify that students use several word-learning strategies during the project-based learning activities. The strategies are definition; asking for word meaning to the teacher or looking up a dictionary, inference; inferring the word meaning from teacher’s explanation, and association; understanding the word from context. Besides, the obstacles that students often encounter are related to lack of time during the learning activities and difficulty in remembering newly found vocabularies. Therefore, a comprehensive evaluation is necessary to improve students’ language learning quality. In addition, further research related to the above-mentioned word-learning strategies are highly recommended to examine its effectiveness.